Liberalisasi Pemikiran Islam: Gerakan Bersama Missionaris, Orientalis dan Kolonialis - Hamid Fahmy Zarkasyi (TSAQAFAH, 2009)
Factually, liberalism in social sciences and politics in Western Civilization has marginalized religion or separated religion from social lives and politics step by step. When liberalism became parts of religious thought of Christianity, Catholic and Protestant, it had subordinated the church under the political interest and humanism, and reduced its theological role in almost all aspects of social lives. Therefore, in liberalism of religious thought, the main problem to be argued is the concept of God (Theology) then doctrine and religious dogma. After that, liberalism argued and separated the relationship between religion and politics (Secularism). Finally, liberalism of religious thought became secularism, and influenced by the wave of postmodernism thought which enhances pluralism, equality and relativism. In its expansive movement, through globalization, modernization, and westernization, the West subsequently becomes the challenge of all nations and other civilization include Islam. Specifically, Western Civilization could be seen from three cultural sources; missionaries, orientalism, and colonialism. These three movements essentially disseminate the principle or element of Western way of life.